Estudo descritivo-analítico do sujeito gramatical no período de 1881-1915 da gramatização brasileira: entre a tradição e a inovação - Andrade, Anderson Monteiro (2019)
The present work is located on the History of Linguistic Ideas line of research and it has as its descriptive and analytical investigation object the grammatical subject represented on the timeline (1881-1915), first phase of the scientific grammar. Our aim with this work is to describe and analyze the grammatical subject inventory (conceptions, definition criteria, typologies) on the grammatical production on the above mentioned period through the works Grammatica Portugueza (1st ed.,1881), by Júlio Ribeiro; Grammatica Analytica (1887), by Maximino Maciel; Grammatica Portugueza (6th ed.,1895), by Alfredo Gomes; Grammatica Portugueza- Higher education (16th ed., 1911), by João Ribeiro; Grammatica da Língua Portugueza (4th ed., 1913), by Pacheco da silva Jr. and Lameira de Andrade; Grammatica Portugueza (3rd ed., 1913), by Hemetério José dos Santos; and Serões Grammaticaes ou Nova Grammatica Portugueza (2nd ed., 1915), by Ernesto Carneiro Ribeiro. Therefore, the objective is to verify if the enrollment of the explored object is, in fact, tied to the Brazilian grammaticography scientific phase, for it materializes ideas which are influenced by the assumption resulting of the historical-comparative linguistics, or if the approaches on the grammatical subject lead to orientations of the greek-latin tradition of philosophical sense. Hence, we trace, initially, a revision of the History of the Linguistic Ideas postulates, as well as about the history and the Brazilian society at the mid of the 19th century until the year 1915. Furthermore, it is discussed the ideas of the subject in light of the greek-latin grammar with highlights to the discussion about the lógos, the ónoma, the rhêma and the hypokeîmenon on the terms of Plato and Aristotle, turning to the alexandrine legacy of grammar doctrine and to the ideas about the subject on the Téknê, of Dionysus and on the treaty about syntax, of Apollonius Dyscolus. Moreover, it is discussed the linguistic thought of Varro, Donato and Priscianus and the doctrinal influences which oriented the Brazilian grammar production on the 19th and beginning of 20th century. Once the theoretical enrollment, the one which subsidized the analysis through the described works, is finished, it is possible to conclude that the analyzed works move between tradition and innovation, once it follows the Aristotelian notion of categorization, conceive the grammatical subject to the philosophical modes because they propose the agentive trace and the notion of referentiality as category imprint, but also, because of the pursuit for breaking with tradition and for being affiliated to the historical-comparative method, conceive the grammatical subject through an inventory in light of modernity by adopting morphological and syntactic criteria on/for the category definition Key-words: History of Linguistic Ideas. First phase of scientific grammar. Grammatical subject. Tradition. Modernity